The relationship between internet addiction and physical activity levels of university students in a province in eastern Turkey - Genc, Ezgi; Pirincci, Edibe (Ios Press, 2024)
BACKGROUND: Internet addiction and physical inactivity are often a major public health problem. OBJECTIVE: This study aimed to determine the relationship between internet addiction (IA) and physical activity (PA) levels of university students in a province in eastern Turkey. METHODS: This cross-sectional study was conducted among 638 students. Internet Addiction Test (IAT), and International Physical Activity Questionnaire (IPAQ) were administered. Chi-square, independent sample t-test, correlation analysis, one-way analysis of variance tests (ANOVA), Tukey HSD test, and multivariate logistic regression analysis were performed. RESULTS: 64.6% of the participants were female, with a mean age of 20.4 +/- 2.4 and a mean body mass index (BMI) of 22.3 +/- 3.5. 83.4% of the participants were identified as those asymptomatic, 15.2% showed limited symptoms, and 1.4% were pathological internet users according to IAT. A statistically significant difference was found between IAT scores and gender, mother's education level, father's education level, academic success, smoking status, and alcohol use (p < 0.05). According to IPAQ scores, 28.1% of the students were inactive, 56.3% were moderate PA and 15.7% had vigorous PA levels. IPAQ total scores of male participants, smokers, and participants with exercise habits were found to be significantly higher (p < 0.05). The mean score IAT and IPAQ was found to be 30.9 +/- 18.9 and 1697.7 +/- 1847.0. A negative, significant correlation was found between students' PA and IA levels (p < 0.01). CONCLUSION: It has been observed that IA negatively affects PA. Seminars, conferences, and panels on the internet and physical activity should be organized for university students.
Keywords: Body mass index; cross-sectional study; exercise; gender; habits; smoking